KOOPERATIF DAN KONFLIK DALAM PENDIDIKAN BERBASIS AGAMA, FILSAFAT, PSIKOLOGI, DAN SOSIOLOGI - Ahmad Yani; Budi Hermawan; Amruddin; Ujang Nurjaman (al-Afkar, Journal For Islamic Studies, 2022)
The purpose of this study is to describe and analyze the what, why, and how of cooperative and conflict in education based on religion, philosophy, psychology, and sociology. The results of this study are that cooperative and conflict in education are cooperation and disputes in the educational process which by: (1) based on religion means being guided by the teachings of God who wants goodness, where cooperation is woven in virtue and piety, energy, closest people, peace , patience and prayer, material and immaterial benefits, while conflicts are handled by deliberation and tahkim (arbitration); (2) based on philosophy means guided by universal knowledge and the meaning of life that requires reconstruction, which is carried out by means of democracy or consensus; (3) based on psychology means being guided by Islamic knowledge of thought and behavior, which is handled through belief, rational, integrated belief and rational methods, and authority methods; and (4) based on sociology means referring to social science as the complexity of social systems, through qualitative approaches (historical, comparative, and case study methods) and quantitative approaches (deductive, inductive, empirical, rational, and functional methods).